AI Chatbot Simulations in Teacher Training: Core Teaching Competencies Developed Through Virtual Practice - Tegero, Maricar C.; Mabini, Jay P. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study examines the role of AI chatbots in simulating real-world teaching scenarios and developing core teaching competencies among pre-service teachers. Guided by the SAMR model, the research employed a single-case qualitative design involving seven Bachelor of Physical Education interns from a teacher education institution in the Philippines. Data were gathered exclusively through focus group discussions, which explored the participants’ experiences using AI chatbots during their practicum. Thematic analysis revealed that chatbot simulations contributed to the development of six key teaching competencies: instructional planning and structuring, content mastery and clarification, designing engaging activities, communication and language precision, reflective practice and pedagogical decision-making, and professional confidence and self-efficacy. Participants described AI chatbots as helpful rehearsal partners that allowed them to clarify concepts, refine lesson plans, anticipate student reactions, and improve instructional language in a low-pressure setting. The chatbot interactions also prompted critical reflection on teaching strategies and enhanced the interns’ confidence before entering the actual classroom. Findings suggest that AI-powered simulations can be meaningfully integrated into teacher education programs to bridge the gap between theory and practice. The study recommends embedding AI-supported activities into practicum courses and providing guidance on the ethical and pedagogical use of AI tools in education.